Effectiveness of the potential development model based on 5As counseling technique on community smoking cessation in nursing student leaders - karunan, kholid; Makchuchit, Satiman; Bunlap, Paseena; Lertariyapongkul, Najmah (Thai Journal of Nursing, 2022)
This quasi-experimental research aimed to evaluate effectiveness of the potential development model based on 5As counseling technique on community smoking cessation in nursing student leaders . A sample of 65 second year nursing students studying at Boromarajonani College of Nursing Yala, and 105 people were purposively selected. The research tools were the potential development model for nursing student leaders, knowledge test, and satisfaction questionnaire on activity management. Percentage, mean, standard deviation, and paired t-test were used in data analysis. Results revealed that after experiment, nursing student leaders gained higher score of knowledge than before experiment at p < .001 ( t = -12.05). Their satisfaction on activity management were rated at high level after experiment (M = 4.18, SD = 0.76). People also felt satisfied with activity management on prevention of cigarette hazard in community at high level (M = 4.38 SD = 0.75).